Presenteeism in multiprofessional team workers in the Adult Intensive Care Unit - Silva,Andressa Fernanda (2019)
ABSTRACT Objective: To analyze the occurrence of presenteeism in multiprofessional team workers of an Adult Intensive Care Unit, relating it to sociodemographic and labor characteristics. Method: It is an analytical cross-sectional qualitative study, which used a questionnaire for sociodemographic data collection, and Stanford Presenteeism Scale(SPS-6) to assess presenteeism. Results: There was predominance of women (75.9%), nursing workers (66.7%), mean age of 39.81 years, and 6 to 10 years (31.6%) of experience in the labor market. Regarding presenteeism, 48.7% presented work impairment and 31.8% presentedperformance and completion of tasks altered by this phenomenon. Conclusion: Expressive numbers of general presenteeism were identified, with results indicating impairment in completing work. When connecting presenteeism to sociodemographic and labor characteristics, the variables sex, dependent children and absence from work presented values with statistical significance among the studied workers.